Homogeneous anisotropic cosmological models with viscous fluid and heat flow in lyra's geometry - Ram S.; Verma M.K.; Zeyauddin M. (My University, 2025)
In this paper, a spatially homogeneous and anisotropic Bianchi type V model filled with an imperfect fluid with both viscosity and heat conduction is investigated within the framework of Lyra's geometry. Exact solutions of the field equations are obtained by applying a special law of variation for Hubble's parameter which yields a constant value of the deceleration parameter. Two different physically viable models of the universe are presented in two types of cosmologies, one with power-law expansion and other one with exponential expansion. Cosmological model with power-law expansion has an initial big-bang type singularity at t = 0 whereas the model with exponential expansion has a singularity in the infinite past. The physical and dynamical properties of the models are discussed. © 2009 World Scientific Publishing Company.